Globalisation and Social Spending - Paul De Grauwe; Magdalena Polan (Center for Economic Studies and ifo Institute (CESifo), 2003)
We provide evidence indicating that countries with well-developed social security systems do not necessarily face a trade-off between social spending and competitiveness. On average, countries that spend a lot on social needs score well in the competitiveness league. We investigate the importance of a reverse causality from competitiveness to social spending, and find that this is weak. We also present some possible explanations for our empirical finding. Finally, we interpret our findings in the framework of a theoretical model in which risk affects the size of the social sector and in which social spending affects the production function of the private sector.
Keywords: 330; economic integration; globalisation; terms-of-trade variability; international trade; globalization